2018
DOI: 10.4274/tjps.86580
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Pelargonium endlicherianum Fenzl. extracts in lipopolysaccharide-stimulated macrophages.

Abstract: Bu çalışma Pelargonium endlicherianum Fenzl. ve Pelargonium quercetorum Agnew. kök ekstrelerinin anti-enflamatuvar etkilerini, ticari Pelargonium sidoides kök ekstresinin etkileri ile kıyaslayarak LPS ile uyarılmış makrofaj hücrelerinde pro-enflamatuvar bileşiklerin üretimi ve enflamatuvar sinyal iletimi yoluyla incelemek üzere dizayn edildi. Gereç ve Yöntemler: Kök ekstrelerinin pro-enflamatuvar aracılar üzerine etkisini ölçmek için takip eden yöntemler kullanıldı: 3-(4,5-dimetiltiazol-2il)-difenil tetrazoliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(36 reference statements)
0
1
0
1
Order By: Relevance
“…[18][19][20]. Использование Умкалора в клинической практике обусловливают следующие доказанные эффекты препарата: антимикробный (антивирусный, антибактериальный, антимикотический и антипротозойный) [21][22][23][24][25], иммуномодулирующий [21,26,27], противовоспалительный [28], улучшение дренажной функции ВДП (муколитический, секретомоторный) [27].…”
Section: Bronchopulmonology Otorhinolaryngologyunclassified
“…[18][19][20]. Использование Умкалора в клинической практике обусловливают следующие доказанные эффекты препарата: антимикробный (антивирусный, антибактериальный, антимикотический и антипротозойный) [21][22][23][24][25], иммуномодулирующий [21,26,27], противовоспалительный [28], улучшение дренажной функции ВДП (муколитический, секретомоторный) [27].…”
Section: Bronchopulmonology Otorhinolaryngologyunclassified
“…It is also used for chronic headaches, neck pains, and migraines [14]. Studies have shown that P. quercetorum has a high content of total phenols and flavonoids, and gallic acid and apocynin have been identified in the root extracts of the plant [16]. Although there are limited studies on this traditionally used plant, it has been shown to cause apoptosis in lung and breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%